Constraining or Constructive? The Effects of Examples on Idea Novelty. (18th May 2017) - George, Tim; Wiley, Jennifer; Koppel, Rebecca H.; Storm, Benjamin C.
Abstract : The tendency to conform to prior examples can be viewed as a form of mental fixation that has negative consequences and limits the scope and quality of designs. Two experiments using the Smith, S. M., Ward, T. B., & Schumacher, J. S. [(1993) Memory & Cognition, 21, 837‐845] toy invention task were conducted to determine whether participants who viewed example toys would subsequently generate toys rated as less novel compared to a control group viewing no examples. Although participants who viewed examples tended to incorporate the example features into their own ideas, the novelty of their ideas was rated as higher than those of the control group. This effect occurred both with no specific instruction regarding the examples (Experiment 1), as well as when specifically instructed to be different from the examples (Experiment 2). These results indicate that examples do not always have a negative impact on creativity, and suggest they may sometimes help lead to more unusual ideas.